Handbook of research on changing dynamics in responsible and sustainable business in the post-COVID-19 era - Popescu, Cristina Raluca Gh., 1983- (Practice, progress, and proficiency in sustainability (PPPS) book series., 2022)
"This book provides an updated view of the newest trends, novel practices and latest tendencies concerning the manner of addressing and creating responsible and sustainable business, while striving to understand those important changes caused by the Covid-19 pandemic shock"--